RITEL MIX DAN KEPUTUSAN PEMBELIAN KONSUMEN : STUDI PADA KONSUMEN TOKO RITEL DI KOTA MADIUN - Alvin Cahya Septiana; Ardianus Laurens Paulus (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2018)
Retail mix is ​​a tool used to implement and handle the development of retail strategies to satisfy the needs of more target markets than competitors. This research was conducted to determine which factors predominantly influence purchasing decisions in retail companies. In addition, this study aims to analyze the influence of retail mix consisting of customer service, store design & display, communication mix, location, merchandise assortment, and pricing of consumer purchasing decisions in retail stores in the city of Madiun. A sample of 100 people with purposive sampling and snowball sampling techniques. Respondents are consumers in retail stores in Madiun City which consist of 3 Sub-Districts namely Taman Subdistrict, Kartoharjo District and Manguharjo District. Multiple linear regression analysis techniques. The results of the simultaneous retail mix research have a significant effect on consumer purchasing decisions. Partially variable store design & display, merchandise assortment, and pricing have a significant positive effect on consumer purchasing decisions. Customer service variables have a significant negative effect on consumer purchasing decisions. Communication mix and location variables have no significant effect on consumer purchasing decisions. Subsequent research needs to include a variable post-purchase behavior because the customer will evaluate the experience after making a purchasing decision.